Fatal revenant. book two : The last chronicles of Thomas Covenant - Donaldson, Stephen R. (Donaldson, Stephen R. Last chronicles of Thomas Covenant, 2007)
Linden Avery finds her missing autistic son, completely cured and in the company of a corporeal Thomas Covenant, only to face the dilemma of whether to use the Earthpower to return herself and her companions to Earth or to save the Land from its enemies.